Explore Westonci.ca, the leading Q&A site where experts provide accurate and helpful answers to all your questions. Experience the convenience of getting reliable answers to your questions from a vast network of knowledgeable experts. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform.

If x^2 - 6xy = z - 9y^2, make x the subject of the formula

Sagot :

[tex]~~~~x^2-6xy=z-9y^2\\\\\implies x^2- 2\cdot x\cdot 3y + (3y)^2 - (3y)^2 = z-9y^2\\ \\\implies (x-3y)^2 -9y^2 = z-9y^2\\\\\implies (x-3y)^2 = z\\\\\implies x - 3y =\pm\sqrt z\\\\\implies x = 3y\pm\sqrt z[/tex]

Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Your questions are important to us at Westonci.ca. Visit again for expert answers and reliable information.